The Association between Fetal Weight and Failure of Labor Progress at the Primigravida at Term - حسن, سحر; يوسف, أحمد; محمد, هناد (Latakia University Journal -Medical Sciences Series, 2020)
Objective: Evaluate the association between fetal weight and failure of labor progress to detect some indications that help us making the right decision at the right time and determining the route of delivery to prevent maternal and fetal complications. Methods: The study sample included 297 pregnant woman with gestational age between 37w-41w6d and admitted to labor department at Tishreen university hospital for vaginal delivery meeting inclusion criteria in this study. women aged 16-35 years old with a median of 25 years. Results: 33 of 297 pregnant women (11.1%) needed C-section due to failure of labor progress, 18 of them (54.5%) was due to cervical dilation arrest and 15 (45.5%) due to descent arrest. no recorded C-sections in the group 2000-2499g (5 patients), 9 C-sections of 81 patients in the group 2500-2999g, 7 C-sections of 105 patients in the group 3000-3499g, 9 C-sections of 71 patients in the group 3500-3999g, 5 C-sections in the group 4000-4499g and 3 C-sections of 6 patients in the group over 4500g so that 24.3% of this C-sections was in the groups of 4000g and over so there is a statistical significance between fetal weight and route of delivery. Of 18 C-sections due to cervical dilation arrest there was 7 (38.9%) in the group 2500-2999g, 6 (33.3%) in the group 3000-3499g, 4 (22.2%) in the group 3500-3999g and 1 (5.6%) in the group 4000-4499g. of 15 C-sections due to descent arrest there was 2 (13.3%) in the group 2500-2999g, 1 (6.7%) in the group 3000-3499g, 5 (33.3%) in the group 3500-3999g, 4 (26.7%) in the group 4000-4499g and 3 (20%) in the group over 4500g. so that 47% of descent arrests happened in the groups over 4000g and 40% of cervical dilation arrests happened in the groups under 3000g so there is a statistical significance between fetal weight and the cause of labor failure (cervical dilation arrest – descent arrest).